1992
DOI: 10.1172/jci115723
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection of liver graft by hepatitis C virus after liver transplantation.

Abstract: We have investigated hepatitis C virus (HCV) viremia before and after orthotopic liver transplantation (OLT). 38 patients were examined; 16 were anti-HCV positive and 22 anti-HCV negative pre-OLT in a RIBA-2 test (Ortho Diagnostic Systems Inc., Westwood, MA). HCV-RNA was detected using a modified nested polymerase chain reaction in 14/38 and 10/38 patients before and after OLT, respectively. 7 of these 14 subjects who were HCV-RNA positive before OLT were also positive for serum hepatitis B surface antigen. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(105 citation statements)
references
References 18 publications
2
103
0
Order By: Relevance
“…It is well established that detectable serum HCV ribonucleic acid, even at a high level, after LT, does not necessarily indicate the presence of histologic RHC. 2,3,13,24 As has been described for recurrent hepatitis B, 25,26 immunosuppression may alter the histological appearance of viral hepatitis after transplantation. Consequently, in posttransplant patients, especially during the first few months when immunosuppression is maximal, classic histopathologic features of hepatitis C may be absent or modified.…”
Section: Discussionmentioning
confidence: 93%
“…It is well established that detectable serum HCV ribonucleic acid, even at a high level, after LT, does not necessarily indicate the presence of histologic RHC. 2,3,13,24 As has been described for recurrent hepatitis B, 25,26 immunosuppression may alter the histological appearance of viral hepatitis after transplantation. Consequently, in posttransplant patients, especially during the first few months when immunosuppression is maximal, classic histopathologic features of hepatitis C may be absent or modified.…”
Section: Discussionmentioning
confidence: 93%
“…With improvements in diagnostic techniques to detect HCV, it has been observed that recurrent HCV infection after OLT is almost universal. 1,2 Feray et al 3 showed a high degree of molecular homology between pretransplantation and posttransplantation viral isolates, confirming that the same strain of HCV is responsible for recurrent viral infection. Furthermore, Chazouilleres et al 4 have shown that the levels of serum HCV RNA increased significantly after OLT, and this is probably caused by the presence of immunosuppression in the postoperative period.…”
Section: Copyright 1998 By the American Association For The Study Of mentioning
confidence: 97%
“…4,6,[8][9][10] Moreover the finding of HBV DNA in peripheral mononuclear blood beyond 12 months of effective HBIG prophylaxis argues in favor of a potentially indefinite risk of graft infection. [11][12][13] As a consequence, most liver transplant centers are currently administering HBIG on a life-long basis. Because HBIG use is highly expensive, an alternative strategy aiming at the discontinuation of HBIG prophylaxis during the second year of treatment would be an important cost-effective measure.…”
Section: It Is Widely Agreed That Hepatitis B Virus Immunoglobulin (Hmentioning
confidence: 99%